2004
DOI: 10.1002/cne.20150
|View full text |Cite
|
Sign up to set email alerts
|

Fiber connections of the lateral valvular nucleus in a percomorph teleost, tilapia (Oreochromis niloticus)

Abstract: Fiber connections of the lateral valvular nucleus were investigated in a percomorph teleost, the tilapia (Oreochromis niloticus), by tract-tracing methods. Following tracer injections into the lateral valvular nucleus, neurons were labeled in the ipsilateral dorsal part of dorsal telencephalic area, corpus glomerulosum pars anterior, dorsomedial thalamic nucleus, central nucleus of the inferior lobe, mammillary body, semicircular torus, valvular and cerebellar corpus, in the bilateral rostral regions of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 65 publications
10
71
2
Order By: Relevance
“…Projections from the pretectum and hypothalamus to the NLV have also been reported in previous studies [Ito and Yoshimoto, 1990;Shimizu et al, 1999;Yang et al, 2004]. The NLV thus may also convey pretectal and hypothalamic inputs to the CC in addition to the telencephalic afferents [Ito and Yoshimoto, 1990;Yang et al, 2004].…”
Section: Afferents From the Mesencephalonsupporting
confidence: 76%
See 2 more Smart Citations
“…Projections from the pretectum and hypothalamus to the NLV have also been reported in previous studies [Ito and Yoshimoto, 1990;Shimizu et al, 1999;Yang et al, 2004]. The NLV thus may also convey pretectal and hypothalamic inputs to the CC in addition to the telencephalic afferents [Ito and Yoshimoto, 1990;Yang et al, 2004].…”
Section: Afferents From the Mesencephalonsupporting
confidence: 76%
“…A telencephalic relay portion of the NLV has been regarded as a separated cell group from the NLV, and was called the dorsal tegmental nucleus in some teleosts [Lepomis and Carassius: Wullimann and Northcutt, 1988;Carassius and Pantodon: Wullimann and Meyer, 1993]. Projections from the pretectum and hypothalamus to the NLV have also been reported in previous studies [Ito and Yoshimoto, 1990;Shimizu et al, 1999;Yang et al, 2004]. The NLV thus may also convey pretectal and hypothalamic inputs to the CC in addition to the telencephalic afferents [Ito and Yoshimoto, 1990;Yang et al, 2004].…”
Section: Afferents From the Mesencephalonmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar findings have been reported in several other studies (10,11,17,18). Thus, we believe that the results for the fish in the A-SAL and S-SAL groups were opposite in terms of memory consolidation of the inhibitory avoidance task due to the absence of cerebellar modulation in limbic structures in the ablation group, especially in the MP, which is thought to be homologous to the amygdala (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
“…The lateral pallium is associated with spatial and temporal memory, and appears to be homologous to the hippocampus of vertebrates, while the medial pallium (MP) is related to emotional memory and has been suggested to be homologous to the amygdala of mammals (28,29). Furthermore, recent studies have demonstrated the existence of connections between the cerebellum and the MP in goldfish and other teleost fish (30,31).…”
Section: Discussionmentioning
confidence: 99%